Exploration And Morphology Identification of Spores Asbuscular Mycorrhizal Fungi from Horticultural Plantation - Eka Susila; Sari Rukmana Okta Sagita Chan; Benny Satria Achmad; Fri Maulina (Green Engineering Society, 2022)
Differences in location and rhizosphere cause differences in species diversity and population of Arbuscular Mycorrhizal Fungi (AMF). In addition, not all AMF have the same morphological and physiological characteristics, therefore it is very important to know their identity. This study aims to determine the presence and number of spores as well as to determine the morphological characteristics of AMF originating from the rhizosphere of several horticultural crops in the agricultural land of Payakumbuh State Agricultural Polytechnic. The method used in this research is descriptive exploratory method by means of purposive sampling for soil sampling. While the stages of this research include: taking and collecting data in the field, determining the point of location for soil sampling, taking soil samples, analyzing soil properties in the laboratory, isolating AMF spores and identifying AMF spores morphologically. The conclusions of this study are 1) The population of AMF spores in horticultural land is high. The highest spore population was found in soil samples of the root area of shallot plants (556 spores per 10 g of soil), while the lowest number of spores was in soil samples of eggplant root areas (271 spores per 10 g of soil), 2) AMF exploration in several horticultural crops in the agricultural land of the Payakumbuh State Agricultural Polytechnic, based on morphological identification (shape, color and size), the AMF found consisted of three genera, namely Glomus sp, Gigaspora sp, and Scutelospora sp.